Performing Strategic Science in the Public Interest: Updating the Policy Debate Regarding Government Science - Kinder, Jeff; Welsh, Frank (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2012)
The performance of science and technology (S&T) activities in the federal government has long been supported as a means of advancing innovation and economic objectives as well as of addressing public policy and regulatory needs. As Canada’s science and innovation system has matured, however, the federal government’s relative contribution to Canada’s overall performance of research and development has declined significantly—from about 30% (of total spending) in 1971 to under 9% today. Throughout this period, a dominant policy theme with respect to government S&T has been to migrate these activities from government into the private or academic sectors. The authors trace this history and argue that science policy thinking regarding federally-performed S&T must evolve with the changing position of government laboratories in Canada’s science and innovation system. A case is made for maintaining an adequate S&T capacity within the federal government in order to deliver on unique public interest roles.